PTH-134 Reduced calcineurin inhibitor exposure early after liver transplantation protects against renal dysfunction independently of the use of basiliximab induction therapy. (22nd June 2015) - Onali, S; Mansell, A; Aspite, S; De Luca, L; Tsochatzis, E; O'Beirne, D. Patch, J; Thorburn, D; Pinzani, M; Manousou, P
Abstract : Introduction: Basiliximab use with delayed entry of Tacrolimus (TAC) as renal sparing agent may help reduce renal impairment in liver transplant (LT) recipients. We aimed to evaluate factors affecting renal dysfunction and the effect of basiliximab post-LT. Method: All consecutive LT patients (1/2006–1/2014) with a follow up >3months and eGFR <90 ml/min/1.73m 2 at day 1 post-LT were analysed for factors known to affect renal dysfunction: biochemical/clinical data, donor age, cold/warm ischemia time, mean trough TAC levels up to days 7, 15, 30 post-LT, basiliximab use, initial/maintenance immunosuppression, acute cellular rejection (ACR), diabetes mellitus (DM) pre and post-LT, systemic hypertension, days on filtration post-LT. Renal impairment was defined as mild: eGFR 60–89 and moderate/severe: eGFR <60. Endpoints were eGFR at 3 months and at last follow up post-LT. Results: 126 patients given basiliximab were compared with 189 consecutive patients with eGFR <90 at day 1 post-LT (control group). Basiliximab group had mean TAC trough levels 3.4ng/ml vs 5.9ng/ml of controls at the first week and 4.2ng/ml vs 6.6 ng/ml respectively at 15 days post-LT. 20(16%) on basiliximab had ACR vs 72/188(38%) controls (p = 0.001). Of those not on basiliximab, 35%(35/97) with TAC levels >5 ng/ml vs 41%(38/92) with TAC <5 ng/ml at week 1 post-LT experienced ACR episodes (p=NS). Logistic regression analysis showed that factors associated with moderate-severe renal impairment (eGFR <60) at 3 months post-LT were: recipient age >50years (p < 0.001, OR=1.06, 95% CI=1.03–1.1), mean CNI levels >5 ng/ml at week 1 post-LT(p = 0.003, OR=0.4, 95% CI=0.3–0.7) and mean CNI levels >7 ng/ml up to 15 days post-LT(p = 0.019 OR=0.85, 95% CI=0.75–0.97). The same factors were associated with mild renal impairment (eGFR <90). Factors associated with moderate/severe renal impairment at last follow up (median 48 m) in the Cox regression analysis were: mean TAC levels >7 ng/ml at days 15 post-LT (p = 0.003 OR=1, 9 95% CI=1.2–2.9) and use of steroids >3months post-LT(p = 0.006, OR=0.7, 95% CI=0.5–0.9). Conclusion: Basiliximab use allows reduced TAC trough levels with less episodes of ACR compared with the control group. However, TAC trough levels <7 ng/ml at 15 days post-LT regardless of basiliximab use, were protective of renal function without predisposing to ACR in patients with renal impairment at baseline. Disclosure of interest: None Declared.